2023
DOI: 10.3390/ijms24108926
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Outcomes of the First Commercialized Human Autologous Ex Vivo Cultivated Oral Mucosal Epithelial Cell Transplantation for Limbal Stem Cell Deficiency: Two Case Reports and Literature Review

Abstract: The first product in the world for ex vivo cultivated oral mucosal epithelial cell transplantation (COMET) to treat limbal stem cell deficiency (LSCD), named Ocural®, was launched in June 2021 in Japan. COMET was performed on two patients, including the first case in the post-marketing phase of Ocural®. Pathological and immunohistochemical examinations were also carried out using specimens obtained before and after COMET and the spare cell sheet. In case 1, the ocular surface remained free from epithelial defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 57 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…It has been reported to achieve 43–67% success rate in restoring the stability of the ocular surface in LSCD [21–23]. In 2023, an early clinical outcomes of the first commercialized human autologous cultivated oral mucosal epithelial cell transplantation have been reported in two cases [24 ▪ ]. A recent study comparing the outcomes of SLET, CLET, and COMET concluded that differences in study population, clinical trial design, and manufacturing, lead to challenges in direct comparisons of these techniques [25 ▪▪ ].…”
Section: Surgical Management Of Limbal Stem Cell Deficiencymentioning
confidence: 99%
“…It has been reported to achieve 43–67% success rate in restoring the stability of the ocular surface in LSCD [21–23]. In 2023, an early clinical outcomes of the first commercialized human autologous cultivated oral mucosal epithelial cell transplantation have been reported in two cases [24 ▪ ]. A recent study comparing the outcomes of SLET, CLET, and COMET concluded that differences in study population, clinical trial design, and manufacturing, lead to challenges in direct comparisons of these techniques [25 ▪▪ ].…”
Section: Surgical Management Of Limbal Stem Cell Deficiencymentioning
confidence: 99%